Analisi Persepsi Dosen Terhadap Perbankan Syariah (Studi Kasus Dosen Fakultas Ekonomi UMN) - Mawaddah Irham (Universitas Islam Negeri Sumatera Utara, 2019)
Perception is the process of one's interpretation of the environment, in this case the perception of Islamic banking. The purpose of this study was to determine how perceptions of UMN economics lecturers on Islamic banking. The method used is a qualitative method. The data used are primary data in the form of a questionnaire. The results of the study provide data that 70% of informants agree with the principles of Islamic banks, that is monotheism. 40% of informants stated neutral and 33% agreed to Islamic bank operations and 44% stated neutral and 40% agreed to the objectives of Islamic banks.